Embracing Piety: Unraveling the Experiences of Urban Salafi Women in Pursuit of Devotion - Diah Ayu Agustina (At-Tafkir, 2023)
This study aims to shed light on piety cultivation among Salafi women through their engagement in studies hosted by the Nurul Iman Mosque in Blok M Square. This study investigates Salafi women's experiences after attending regular studies at Nurul Iman Mosque as a center for spirituality and Sunnah studies for urban areas in nurturing Salafi women's piety. This study argues that Salafi women who actively participate in mosque studies have a profoundly positive impact on their own piety, spirituality, and overall well-being. The study reveals that mosque studies act as a catalyst for change, nourishing the soul and creating a strong bond with the God. These women receive comfort, inspiration, and information that strengthens their religious commitment through the numerous studies offered. Mosques serve as social gathering places that promote a sense of sisterhood and belonging while providing a safe area for spiritual inquiry and self-improvement. This study also emphasizes the value of mosque studies in motivating urban Salafi women to reflect on and enhance their lives. Through sermon teachings and reminders, women are encouraged to evaluate their behavior and strive for ongoing growth in pursuing piety